Four new species of the genus Smaragdina Chevrolat, 1836 from China (Coleoptera: Chrysomelidae: Cryptocephalinae: Clytrini) - Wang, Feng-Yan; Zhou, Hong-Zhang (Zootaxa, 2013)
Four new species are described for the genus Smaragdina, from Sichuan, Yunnan and Zhejiang provinces of China: Smaragdina tianmuensis sp. nov., S. yajiangensis sp. nov., S. yangae sp. nov., and S. zhangi sp. nov. The Chinese fauna of the genus is thus increased to 64 species. Color plates and line drawings of habitus, maxilla, labium, as well as those characters from the internal morphology like male genitalia, female spermatheca, and rectal sclerites are provided.